Atrophy of myoepithelial cells in parotid glands of diabetic mice; detection using skeletal muscle actin, a novel marker() - Nashida, Tomoko (Elsevier, 2013)
In mouse parotid glands, we found expression of skeletal muscle actin (actin-α1) protein and mRNA. We isolated myoepithelial cells from the mouse parotid glands and investigated their actin-α1 expression because smooth muscle actin (actin-α2) has been used as a marker for myoepithelial cells. We used actin-α1 expression to identify pathological changes in diabetic non-obese diabetic (NOD; NOD/ShiJcl) mice—a mouse model for Sjögren's syndrome—and found myoepithelial cells to be decreased or atrophied in the diabetic state.